2010
DOI: 10.1111/j.1346-8138.2010.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of guttate psoriasis: Long‐term follow‐up study

Abstract: Guttate psoriasis, known to have a better prognosis than other types of psoriasis, shows rapid involution and longer remission, but its clinical course has barely been studied. The aim of this study was to determine the clinical course and to compare the clinical and laboratory features of guttate psoriasis. This is a retrospective study of 26 patients with guttate psoriasis. The patients were divided into two groups; the good one with complete remission and long remission for at least 1 year (group A) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 21 publications
1
46
1
2
Order By: Relevance
“…AGP occurs more frequently in childhood, and a recent study of 314 patients seen in childhood with guttate psoriasis still had it in adulthood [4] . Maybe there are 2 forms of evolution of an AGP over the years as was proposed in previous works [5] , but this does not necessarily involve a change of clinical type. The patients with CR and IR in our study showed some significant differences which could promote 2 different clinical courses, spontaneous healing or chronicity in outbreaks.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…AGP occurs more frequently in childhood, and a recent study of 314 patients seen in childhood with guttate psoriasis still had it in adulthood [4] . Maybe there are 2 forms of evolution of an AGP over the years as was proposed in previous works [5] , but this does not necessarily involve a change of clinical type. The patients with CR and IR in our study showed some significant differences which could promote 2 different clinical courses, spontaneous healing or chronicity in outbreaks.…”
Section: Discussionmentioning
confidence: 95%
“…Traditionally, patients with AGP have been divided into 2 groups in terms of prognosis, one showing CR and the other progressing into chronic plaque psoriasis without complete involution [20] . The exact percentage of AGP progressing into chronic plaques is not clear and varies in the studies from approximately 15-30% [4] to 68% with a follow-up period up to 10 years [5,[20][21][22][23] . In contrast, none of our patients with more than 1 flare of psoriasis (n = 43) presented another clinical type of psoriasis despite being adults with a mean evolution of 6.62 years.…”
Section: Discussionmentioning
confidence: 99%
“…2 Of psoriasis, guttate psoriasis is a distinct eruptive dermatosis that classically occurs in children and young adults following upper respiratory tract infection. 3 It might present as either the initial manifestation of psoriasis in individuals previously unaffected by psoriasis or as an acute exacerbation in individuals with pre-existing chronic plaque psoriasis. Guttate psoriasis is strongly associated with antecedent or concomitant streptococcal infection and of-ten occurs 1 to 2 weeks after streptococcal pharyngitis or a viral upper respiratory infection.…”
Section: Introductionmentioning
confidence: 99%
“…6 Although, limited information is available about the long-term prognosis of individuals with first-manifestation of guttate psoriasis. 5 Ko et al 3 reported that patients have two distinguishable clinical courses, a rapid involution course with longterm remission and a chronic course without remission. Others reported that approximately 33% of patients with guttate psoriasis might eventually develop chronic plaque psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…In genetically susceptible individuals, innate immune mechanism activation and stimulation of T cells trigger psoriasis but the exact stimulus is still unknown (Fry and Baker, 2007;Roberson and Bowcock, 2010). Although streptococcal infections are reported to be the causative agent in guttate form, other infectious agents are still in search (Ko et al, 2010).…”
Section: Introductionmentioning
confidence: 99%